2014
DOI: 10.4239/wjd.v5.i2.165
|View full text |Cite
|
Sign up to set email alerts
|

Origin and therapy for hypertriglyceridaemia in type 2 diabetes

Abstract: Hypertriglyceridaemia (HTG) is a risk factor for cardiovascular disease (CVD) in type 2 diabetes and is caused by the interaction of genes and non-genetic factors, specifically poor glycaemic control and obesity. In spite of statin treatment, residual risk of CVD remains high in type 2 diabetes, and this may relate to HTG and atherogenic dyslipidemia. Treatment of HTG emphasises correcting secondary factors and adverse lifestyles, in particular, diet and exercise. Pharmacotherapy is also required in most type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 128 publications
2
10
0
Order By: Relevance
“…Enhanced triglycerides, serum LDL, total cholesterol, and reduced HDL have also been described as characteristic alterations in diabetic patients posing a major risk factor for cardiovascular events [26, 6163]. Our results demonstrated that CmNo1 significantly attenuated triglycerides, LDL and TC while escalated the HDL levels in DN mice suggesting their anti-atherosclerotic action (Fig 7) [50].…”
Section: Discussionsupporting
confidence: 66%
“…Enhanced triglycerides, serum LDL, total cholesterol, and reduced HDL have also been described as characteristic alterations in diabetic patients posing a major risk factor for cardiovascular events [26, 6163]. Our results demonstrated that CmNo1 significantly attenuated triglycerides, LDL and TC while escalated the HDL levels in DN mice suggesting their anti-atherosclerotic action (Fig 7) [50].…”
Section: Discussionsupporting
confidence: 66%
“…The TG level is further augmented by the loss of activity in LPL due to increased production of apoCIII (a physiological inhibitor of LPL). What is more, due to alterations in lipid transfer by CETP, LDL cholesterol particles in those patients become very atherogenic -"small dense LDLs" [16]. Finally, in patients with significantly elevated glycaemia, an ongoing glycation and oxidation of lipoproteins is responsible for the acceleration of atherosclerosis and its complications [17].…”
Section: Poorly Controlled Diabetesmentioning
confidence: 99%
“…CMs and liver-derived very-low-density lipoproteins (VLDL) compete for delipidation by lipoprotein lipase (LPL) and for subsequent saturable hepatic remnant removal (5,6). In IR, lipoprotein clearance is diminished, in part due to decreased LPL activity, altered lipoprotein composition, reduced hepatic clearance and remnant removal or increased TRL pool size resulting in more competition for clearance (7). In addition, insulin mediated activation of LDLR-related protein-1 which is involved in CM remnant clearance is blunted in insulin-resistant mice (8).…”
Section: Introductionmentioning
confidence: 99%